SELF CONCEPT AND SELF EFFICACY AS A GROUND POINTS IN A SOCIAL ACTIVITIES (AN ANALYSIS OF PSYCHOLOGY PERSPECTIVE : A SOCIAL COGNITIVE THEORY) (Jurnal Pelangi : Research of Education and Development, 2015)
Self Concept and Self Efficacy As A Ground Point In A Social Activities (An Analysis Of Psychology Perspective : A Social Cognitive Theory). This analysis was based on the latest research in 2014 which concern of researcher about education system number 20th 2003  “... an intelligence and a capabilities that they need  for people and a nation”. Education not only as transfer of knowledge but an experience, readiness and such a faith to a self capabilities and self identity of a student in their social activities like a career readiness. A faith of capabilities is known as self efficacy and self identity is a self concept. These variable was tested at research in 2015 and has been found that these variable has a contribution to career readiness. Analysis is continued to discuss and note as a ground point in social activities in psychology perspective. It’s found a self concept and self efficacy together have a contribution to a career readiness with a significant correlation, although in coefficient t-tes not have a significant. Then, there was a significant effects of all variables to career readiness. In a social cognitive theory perspective, human can be learn only through observation and interaction that shape a self concept and self efficacy. This found will be analyze and describe as a self concept and self efficacy as s ground point in social activities. So this analysis will discuss further the implication to individual social activities like a career readiness with using psychology perspective: Social Cognitive Theory.